Yolk color and sensory analysis of eggs of common quails (Coturnix coturnix coturnix) fed sorghum-based diet with the addition of annatto seed meal (Bixa orellana L.) - Lima, Daniela Nogueira (2022)
This study has aimed to assess the effect of increasing levels of annatto (Bixa orellana L.) seed meal (AM) on yolk pigmentation and the sensory analysis of eggs of common quails fed sorghum-based diets when compared to corn. Eighty female common quails (Coturnix coturnix coturnix) in the laying phase were used, being them aged from 251 to 316 days. There were three experimental periods of 21 days each (251-272; 273-294; 295-316 days). The quails were distributed in a completely randomized design with five treatments (T1 - corn-based feed; T2 - feed with 100% of sorghum instead of corn without the addition of AM; T3, T4, and T5 - feed with 100% of sorghum replacing corn with the addition of 0.5, 1.0, and 1.5% AM, respectively) and four repetitions. One hundred eggs from each treatment were used for analysis. Sensory evaluation was applied with an untrained panel with 20 evaluators. The eggs were boiled, peeled, and served. The panelists assessed the appearance, flavor, color, aroma, texture, and overall evaluation of the eggs. Annatto seed meal added to sorghum-based diets promoted linear increases in appearance, flavor, color, aroma, texture, and overall evaluation, evaluated during the sensory analysis (p=0.001). The addition of 1.5% AM in the sorghum-based diets of the common quails benefited the characteristics of appearance (4.50), flavor (4.50), color (4.55), aroma (4.25), and texture (4.55) of the assessed quail eggs, being considered more attractive and with greater acceptance (overall evaluation = 5.97) in relation to the other treatments tested. The inclusion of AM in the sorghum-based diets improved the yolk pigmentation of quail eggs in relation to the control treatments. The AM triggers positive effects on yolk pigmentation and sensory characteristics of common quail eggs.